Graft‐infiltrating PD‐L1hi cross‐dressed dendritic cells regulate antidonor T cell responses in mouse liver transplant tolerance. Issue 4 (18th February 2018) - Ono, Yoshihiro; Perez‐Gutierrez, Angelica; Nakao, Toshimasa; Dai, Helong; Camirand, Geoffrey; Yoshida, Osamu; Yokota, Shinichiro; Stolz, Donna Beer; Ross, Mark A.; Morelli, Adrian E.; Geller, David A.; Thomson, Angus W.
Abstract : Although a key role of cross‐dressing has been established in immunity to viral infection and more recently in the instigation of transplant rejection, its role in tolerance is unclear. We investigated the role of intragraft dendritic cells (DCs) and cross‐dressing in mouse major histocompatibility complex (MHC)‐mismatched liver transplant tolerance that occurs without therapeutic immunosuppression. Although donor interstitial DCs diminished rapidly after transplantation, they were replaced in the liver by host DCs that peaked on postoperative day (POD) 7 and persisted indefinitely. Approximately 60% of these recipient DCs displayed donor MHC class I, indicating cross‐dressing. By contrast, only a very minor fraction (0%‐2%) of cross‐dressed DCs (CD‐DCs) was evident in the spleen. CD‐DCs sorted from liver grafts expressed much higher levels of T cell inhibitory programed death ligand 1 (PD‐L1) and high levels of interleukin‐10 compared with non–CD‐DCs (nCD‐DCs) isolated from the graft. Concomitantly, high incidences of programed death protein 1 (PD‐1) hi T cell immunoglobulin and mucin domain containing 3 (TIM‐3) + exhausted graft‐infiltrating CD8 + T cells were observed. Unlike nCD‐DCs, the CD‐DCs failed to stimulate proliferation of allogeneic T cells but markedly suppressed antidonor host T cell proliferation. CD‐DCs were much less evident in allografts from DNAX‐activating protein of 12 kDa (DAP12) −/− donors that were rejected acutely. Conclusion : These findings suggest that graft‐infiltrating PD‐L1 hi CD‐DCs may play a key role in the regulation of alloimmunity and in the induction of liver transplant tolerance. (Hepatology 2018;67:1499‐1515)